A projection and contraction method for symmetric cone complementarity problem. (2nd November 2019) - Liu, Sanyang; Liu, Xiangjing; Chen, Junfeng
ABSTRACT: This paper considers the symmetric cone complementarity problem. A new projection and contraction method is presented which only requires some projection calculations and functional computations. It is proved that the iteration sequence produced by the proposed method converges to a solution of the symmetric cone complementarity problem under the condition that the underlying transformation is monotone. Numerical experiments also show the effectiveness of this method.